If you mean: 3x-3y = 9 and y-3x = -3 then by adding both equations y = -3 and by substitution x = 0
If you mean x+2y = -2 and 3x+4y = 6 then by solving the simultaneous equations by substitution x = 10 and y = -6
y= -4x-7 y=3x 3x= -4x-7 3x+4x=7 7x=7 x=1
You solve one of the equation for one of the variables. For example, if the variables involved are "x" and "y", you might solve for "y". It doesn't really matter what variable you solve for first, so you can solve for whatever variable is easiest to solve. Then - assuming you got, for example, "y = 3x -1", in this example you would replace every "y" by "3x - 1" in the other equation or equations.
Can you help me find the value x & Y 3x + 7y = 5 5x-2y = -19
Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4
If you mean: x+7y = 39 and 3x-2y = 2 Then by substitution: x = 4 and y = 5
It is not possible to do so because the question contains one equation (5x + y = 1) and one expression (3x + 2y + 2). An expression cannot be solved.
From second equation: y = 8 + 2xSubstitute for y in first equation: 3x + 16 + 4x = 2ie 7x = -14ie x = -2 and y = 4
From first equation: y = 5 - 5xSubstitute for y in second equation: 3x + 10 - 10x = 3ie -7x = -7ie x = 1 and y = 0
4x-y=2, thereforey=4x-2sub y into 3x+2y=6...3x+8x-4=611x=10x=10/11
-3x = 3 + y 3 + y - 5y = -21 -4y = -24 y = 6 x = -3
(3x - 1)(3x + 19)
3x + 2y = 12 ie 2y = 12 - 3x so y = 6 - 3x/2
You can't solve 5x+3x there isn't a equal sign. But you can simplify it to be 8x
solve system equation using addition method 3x-y=9 2x+y=6
you cant solve but you can simplify -55x
what does the equation equal? if it equals zero: 0= 3x(4-11) 0=3x(-7) 0=3x 0=x if the equation doesn't equal anything, it means it's just an expression meaning you can't solve for x, you can only reduce (and this equation is already reduced). if the equation equals y, you need another equation and use either substitution or elimination to solve for x.
6x + 4 = 3x + 19 3x + 4 = 19 3x = 15 x = 5 Check it. 30 + 4 = 15 + 19 It checks.
If you mean: 3x-4y = 19 and 3x-6y = 15 Then: x = 9 and y = 2
Baisiclyy 3x-1 3x-1 ____ 9x-1 then the answer is 8x :)